IMPLEMENTASI PERATURAN DAERAH NO 9 TAHUN 2013 TENTANG PENANGANAN ANAK JALANAN, GELANDANGAN DAN PENGEMIS (STUDI PADA DINAS SOSIAL KOTA MALANG) - Wilenda Yudha Pratama Afjan; Hayat Hayat (Halu Oleo University, 2023)
The purpose of this research is to find out, describe and analyze the Implementation of Regional Regulation No. 9 of 2013 concerning the Handling of Street Children, Homeless, and Beggars (Policy Study at the Malang City Social Service) accompanied by the results of a research study on the supporting and inhibiting factors of its implementation. This study uses a descriptive qualitative research method. Data was obtained through observation, interviews, documentation, and triangulation. The data validity testing procedure was carried out by triangulating the source data analysis process using the model proposed by Miles and Huberman. The results of this study indicate that in terms of the Implementation of Regional Regulation No. 9 of 2013 concerning the Handling of Street Children, the Homeless, and Beggars (Policy Studies at the Malang City Social Service) studied through the theory of the Van Meter Van Horn implementation model has not been fully said to be good. From the application of the implementation of Regional Regulation No. 9 of 2013 concerning the Handling of Street Children, Homeless and Beggars (Policy Study at the Malang City Social Service) there are also inhibiting and supporting factors. Factors supporting the implementation are adequate resources and the existence of the Liponsos Camp Assessment Shelter, while the inhibiting factors are the condition of mobile social welfare problems and the absence of SOP raids from social services